Heterogeneity in deformation of granular ceramics under dynamic loading. (15th January 2016) - Huang, J.Y.; Lu, L.; Fan, D.; Sun, T.; Fezzaa, K.; Xu, S.L.; Zhu, M.H.; Luo, S.N.
Graphical abstract: Abstract: Dynamic compression experiments are conducted on micron-sized SiC powders of different initial densities with a split Hopkinson pressure bar. Digital image correlation is applied to images from high-speed X-ray phase contrast imaging to map dynamic strain fields. The X-ray imaging and strain field mapping demonstrate the degree of heterogeneity in deformation depends on the initial powder density; mesoscale strain field evolution is consistent with softening or hardening manifested by bulk-scale loading curves. Statistical analysis of the strain probability distributions exhibits exponential decay tail similar to those of contact forces, which are supposed to lead to the grain-scale heterogeneity of granular materials.